Lexical Cohesion Devices in Students’ Narrative Text and Its Pedagogigal Implication in Language Teaching: A Discourse- Semantics Point of View - Darong, Hieronimus Canggung; Jem, Yosefina Helenora; Guna, Stanislaus (FKIP Universitas Lampung, 2022)
Lexical Cohesion Devices in Students Narrative Text and Its Pedagogical Implication in Language Teaching: A Discourse- Semantics Point of View. Objective: This study aims at examing the lexical devices used in college students’ narrative writing. Method: Each students was requested to compose a free-topic narrative text which were subsequently analyzed following the principles of discourse- semantic analysis framework. Findings: Although the use of conjunction and reference contributed to the cohesiveness, the results still confirmed that the lexical relations distributed within the texts did not suit with the linguistic environment of the texts. Conclusion: Referring to the findings, the texts constructed by the students were not really being cohessive. As an implication, in language teaching, teachers and learners should pay attention on the use of cohesive devices to create more and better logical writing. Keywords: text, lexical device, cohesive, teaching.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202228